Loss of gastric gland mucin‐specific O‐glycan is associated with progression of differentiated‐type adenocarcinoma of the stomach. Issue 1 (22nd November 2013) - Shiratsu, Kazuo; Higuchi, Kayoko; Nakayama, Jun
<x xml:space="preserve">Abstract</x> Gastric gland mucin secreted from the lower portion of the gastric mucosa contains unique O‐linked oligosaccharides having terminal α1, 4‐linked N‐acetylglucosamine (αGlcNAc) residues largely attached to a MUC6 scaffold. Previously, we generated A4gnt‐deficient mice, which totally lack αGlcNAc, and showed that αGlcNAc functions as a tumor suppressor for gastric cancer. Here, to determine the clinicopathological significance of αGlcNAc in gastric carcinomas, we examined immunohistochemical expression of αGlcNAc and mucin phenotypic markers including MUC5AC, MUC6, MUC2, and CD10 in 214 gastric adenocarcinomas and compared those expression patterns with clinicopathological parameters and cancer‐specific survival. The αGlcNAc loss was evaluated in MUC6‐positive gastric carcinoma. Thirty‐three (61.1%) of 54 differentiated‐type gastric adenocarcinomas exhibiting MUC6 in cancer cells lacked αGlcNAc expression. Loss of αGlcNAc was significantly correlated with depth of invasion, stage, and venous invasion by differentiated‐type adenocarcinoma. Loss of αGlcNAc was also significantly associated with poorer patient prognosis in MUC6‐positive differentiated‐type adenocarcinoma. By contrast, no significant correlation between αGlcNAc loss and any clinicopathologic variable was observed in undifferentiated‐type adenocarcinoma. Expression of MUC6 was also significantly correlated with several clinicopathological variables in differentiated‐type adenocarcinoma. However, unlike the case with αGlcNAc, its expression showed no correlation with cancer‐specific survival in patients. In undifferentiated‐type adenocarcinoma, we observed no significant correlation between mucin phenotypic marker expression, including MUC6, and any clinicopathologic variable. These results together indicate that loss of αGlcNAc in MUC6‐positive cancer cells is associated with progression and poor prognosis in differentiated, but not undifferentiated, types of gastric adenocarcinoma.